The distribution, expression pattern and effects of TNF superfamily members BAFF and APRIL in Atlantic salmon (Salmo salar L.) and salmon derived leukocytes - Wold, Mikael Fjeld (UiT The Arctic University of Norway, 2018)
Viral disease is one of the greatest challenges facing the aquaculture industry. The most serious disease at the moment is pancreas disease, caused by the salmonid alphavirus (SAV). Substantial efforts are being put into combating the disease, and fish are routinely vaccinated before being put at sea. In theory, vaccines should produce sufficient protection, but performance has been disappointing at a commercial scale. Atlantic salmon (Salmo salar) intrinsically possess a robust immune system. A better understanding of the mechanisms involved in host defenses upon viral infection may contribute to the development of effective therapeutic treatments. The tumor necrosis factor superfamily (TNFSF) of receptors and ligands regulate several aspects of cell functions including immune response and inflammation The B cell activating factor (BAFF) and a proliferation inducing ligand (APRIL) are TNFSF members regulating B cell function, and have in mammals shown to be important in the mounting of an efficient antibody responses upon infection. Understanding the functions of these cytokines in fish may prove useful in future vaccine development. In this work, the distribution and expression patterns of BAFF, APRIL and their receptors are reported for the first time in Atlantic salmon. By transcriptional analyses we determined that the cytokines and their receptors were constitutively expressed in salmon systemic organs. Furthermore, we found that the transcriptional levels of BAFF and APRIL were induced in SAV-infected fish, implicating an integral role of BAFF and APRIL in viral immune responses. In-vitro investigations revealed that macrophage-like cells (MLCs) transcribe both BAFF and APRIL constitutively, although BAFF seems to be the dominant cytokine under normal physiological conditions. Unlike what has been reported in higher vertebrates, but consistent with what has been reported in trout, we found that resting B cells were able to transcribe both cytokines at significant levels. This mechanism may indicate unique ...